The effect of long-haul COVID-19 toward domains of the health-related quality of life among recovered hospitalized patients - Trihandini, Indang; Muhtar, Manendra; Karunia Sakti, Dea Allan; Erlianti, Chintya Putri (Frontiers in Public Health, 2023)
Abstract Background: People with long-haul COVID-19 could experience various health problems, from mild to severe. This research aimed to identify the effect of long-haul COVID-19, specifically on the Quality of Life domains experienced by COVID-19 patients who have been discharged. Method: Data collection was done online, using data from DKI Jakarta hospitalized patients confirmed with and recovered from SARS-CoV-2 infections. We selected patients who have a minimum of 28 days after being hospitalized for COVID-19 positive. The Logistic regression technique was used to analyze the data. The questionnaire used in this research contained questions regarding long-haul COVID-19 symptoms and domains of Quality of Life, which WHOQOL-BREF measured. Before collecting data, we tested the questionnaire with 30 recovered patients hospitalized outside DKI Jakarta. Result: 172 recovered inpatients who filled out the questionnaire correctly and were aged 18 years and above were randomly selected. Almost one-third (30.2%) of the recovered inpatients had long-haul COVID-19, with 23.8% experiencing one long-haul symptom and 6.4% experiencing more than one symptom. This research also showed that the long-haul effects of COVID-19 affected almost all domains of Quality of Life except the environmental one. Age, gender, and marital status were covariates for the association between long-haul COVID-19 and The Quality of Life. Conclusion: Continuing health services after the patient is discharged from the hospital is an important program for COVID-19 survivors because it can prevent a decline in the Quality of Life among patients due to the long-haul COVID-19.